The Global Trade in E-Waste: A Network Approach. Issue 1 (2nd January 2021) - Theis, Nicholas
ABSTRACT: Electronic waste trade is a global environmental injustice issue. Electronic waste is composed of precious metals, making its recycling and reuse economically viable. Yet, it contains hazardous components that threaten the health of ecosystems and human communities. This study uses social network analysis to analyze international trade in environmental context, specifically the global trade in electronic waste. While previous quantitative analyses of ecologically unequal exchange address the environmental impacts of trade, this study focuses on the factors encouraging trade formation in the first place. In so doing, concepts from ecologically unequal exchange and world polity theory are placed in network terms using network inferential techniques. Results indicate that countries in the same income group and region are more likely to form trade relationships than across groups, providing support for world polity theory. However, only a few countries receive a disproportionate amount of electronic waste, and these countries tend to be semi-peripheral nations, providing support for ecologically unequal exchange. In conclusion, I describe how the use of network models to understand ecologically unequal exchange complements standard regression techniques, as the emphasis on relationships illuminates hidden patterns of trade.